Pengaruh Kompensasi dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan PT. Enseval Putera Megatrading (Persero) Tbk Cabang Pekanbaru - Muhammad Fadil Rinaldi; Dewita Suryati Ningsih; Chairul Amsal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to explain the variable of Compensation and Working Environment on employee job satisfaction PT. Enseval Putera Megatrading (Persero) Tbk pekanbaru Branch and to determine which variables are dominant influences between two variables, influence Compensation and Working Environment simultaneously or partially on Employee Job Satisfaction in PT. Enseval Putera Megatrading (Persero) Tbk pekanbaru Branch. Method for collecting the samples is census sampling, the method that all members of the population are sample, 47 people. Data collection methods used were interview, documentation and questionnaire for employees in accordance with the research conducted. Method of Multiple Regression Analysis using SPSS 17.0 version. The results showed that Compensation and Working Environment significantly impact toward Employee Job Satisfaction in PT. Enseval Putera Megatrading (Persero) Tbk pekanbaru Branch. Contribution of the effect of the variable compensation and working environment toward employee job satisfaction in PT. Enseval Putera Megatrading (Persero) Tbk Pekanbaru Branch is 63.5% while 36.5% is influenced by other variables that not included in this study.Keywords : Compensation, Working Environment and Job Satisfaction